239PImpact of counseling on patient reported sexual adjustment following chemoradiation and brachytherapy for cervical cancer. (24th November 2019) - Pareek, V; Bhalavat, R; Chandra, M
Abstract: Background: The treatment of locally advanced cervical cancer with definitive chemoradiation (CRT) is associated with vaginal toxicity and altered sexual satisfaction. This prospective study compared patient-reported sexual adjustment, vaginal dosimetry, and physician-reported vaginal toxicity in patients with cervical cancer treated with CRT and brachytherapy (BT) following counselling for vaginal dilatation or resuming sexual activities with those who did not comply. Methods: Between 2016 and 2018, histopathologically proven and staged IB-IVA patients with cervical cancer receiving definitive CRT were enrolled in a feasibility study assessing the impact of compliance and its outcome in terms of sexual adjustment. Patients completed the validated sexual adjustment questionnaire (SAQ) and EORTC CX24 before BT (baseline) and during follow-up. Physician-reported vaginal toxicity was recorded. Dosimetric analysis was done with focus on rectovaginal point, mean vaginal dose, and D2cm3 .A multivariable linear mixed-effects model was used to examine the association between total and individual scores (repeated measures) and covariates. Results: A total of 75 patients complied with the counselling in terms of either resuming sexual activities or using vaginal dilators as compared to 65 patients who did not use any intervention in spite of the counselling. The diagnosis of cervical cancer and treatment negatively impacted sexual relationships in 66% and 68%, respectively. However, counselling and intervention helped improve the sexual adjustment over time (p = 0.023). There were no associations between sexual adjustment and the ICRU defined Measurements of rectovaginal point dose or clinical vaginal involvement. Stage (p < 0.001), age (p = 0.012) and diabetes (p = 0.037) were found to have an important association with delayed adjustments post intervention. Conclusions: Vaginal stenosis is an important late toxicity associated with radiation therapy and in India, counselling patients for resuming sexual relations can be a taboo. However, our study indicates good compliance among patients for use of intervention to prevent such complications and improved outcomes have been seen. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.